EVALUASI PENGELOLAAN ADMINISTRASI PADA SATPOL PP UNTUK MENINGKATKAN PELAYANAN PADA MASYARAKAT DI KABUPATEN PROBOLINGGO - Mishul Sauliyah Fitriawati; Dwi Orbaningsih; Sungkono (Faculty of Islamic Economics and Business, 2022)
ABSTRACT The Civil Service Police Unit (Satpol PP) is one of the government officials who is a line element that is always at the forefront of maintaining the mandate of Regional Regulations and is always in direct contact with the community. Order and peace in society are things that are highly coveted, both by state administrators, in this case the government, as well as the community itself and for the creation of order and peace, this certainly cannot be separated from the role of Satpol PP in collaboration with other law enforcement agencies. Therefore, the affairs of order and peace are also left to the Satpol PP in order to maximize the socialization of legal products, especially Regional Regulations, Probolinggo Regency Government Regulations, Probolinggo Regency Government Decrees and other legal products in carrying out the wheels of Government in the region to the community. This research uses a qualitative approach that produces descriptive data, this type of research is descriptive research. The place of this research was in the Head of Security and Escort in the Civil Service Police Unit, Probolinggo Regency. In this study, the researcher used a qualitative research method which was designed in three stages, namely interviews, observation and documentation. In conducting this research, the required data were obtained from two sources, namely: primary data and secondary data. The results of this study concluded that to carry out the duties of both daily activities and administrative tasks, the Probolinggo District Civil Service Police Unit in addition to functional positions also formed sub-sections that were responsible for their duties and functions, especially in the field of administration. each individual member of the organization is provided with good training to support their performance. Employees who are proven to have decreased performance are to provide clear feedback and find out the cause of the decline in performance. As a boss always get used to appreciate every improvement.